Degradation of dibenzodioxin during chlorine dioxide bleaching of kraft pulp - Daube, A.K.; Karim, M.R.; Dimmel, D.R.; McDonough, T.J.; Banerjee, S. (1992)
The degree of sorption of dihenzodioxin (DBD) to pulp varies with the lignin content of the latter. DBD is rapidly degraded by chlorine dioxide in aqueous solution but is much more stable in the presence of semibleached pulp, suggesting that sorbed DBD is far less reactive than the freely dissolved material. Degradation products include the 2-chloro derivative and products inextricably bound to pulp. Â© 1992 American Chemical Society.